DESIGN OF TORSIONAL MODULUS EXPERIMENT TOOLS FOR BASIC PHYSICAL EXPERIMENT - Widyastuti, Widyastuti (At-Taqaddum, 2019)
One can explain the material torque through a device called a torsional modulus. The Physics Laboratory of the Faculty of Science and Technology of UIN Walisongo Semarang does not yet have a torsional modulus experiment. With this torsional modulus experiment tool can increase the amount of experiment inventory and can be used as a means of supporting experiment in explaining the concept of torque. The purpose of this research is to design the torsional modulus experiment tool and compile the torsional modulus experiment guide so that it can be used in basic physics experiment courses in the physics laboratory of FST UIN Walisongo Semarang. The design of torsional modulus experiment tools developed with the Research and Development (R&D) procedure has been tested with a very high validity category. The design of the torsional modulus experiment guide has been tested with a very high validity category.